ACCOUNT REPRESENTATIVE SEBAGAI JEMBATAN KEPATUHAN WAJIB PAJAK - Puspita, Ismayantika Dyah; Puspita, Erna; Paramitha, Dyah Ayu (LP2M Institut Teknologi dan Bisnis Asia Malang, 2017)
The purpose of this study are (1) To find out how far understanding taxpayers about Account Representative. (2) Analyzing the socialization conducted by KPP Prataa Pare and Kediri to prospective taxpayers about Account Representative duties. (3) Analyzing to what extent the utilization of AR by the taxpayer. (4) Analyze the implementation of AR tasks in relation to improve taxpayer compliance. This research approach uses qualitative research with phenomenological paradig. Informants are taxpayers registered in KPP Pratama Pare and Kediri with data collection using observation techniques, interviews and documentation. Conclusion of research result is the taxpayer’s informant has no knowledge about AR nor the duties. Taxpayer informants also never get socialization abaout AR and duties of KPP. So the taxpayer does not utilize the service facility of AR, although one of the informants in the end get the service facility during the tax amnesty. So, it can be said that Account Representative (AR) is not the main cause of taxpayer (WP) compliance in carrying out its tax obligations.